2010
DOI: 10.1158/0008-5472.can-09-1681
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Breast Cancer Stem Cell Activity by Signaling through the Notch4 Receptor

Abstract: Notch receptor signaling pathways play an important role not only in normal breast development but also in breast cancer development and progression.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
444
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(472 citation statements)
references
References 37 publications
22
444
2
4
Order By: Relevance
“…Our data demonstrate an essential cell autonomous role of Notch1 in breast CSCs expansion. Harrison et al 42 has reported that Notch4 also affects breast CSCs. They performed knockdown of Notch paralog (Notch1 and Notch4) using both ESA þ / CD44 þ /CD24 low and mammosphere prepared from MCF-7 cells, although Notch ICD overexpression was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate an essential cell autonomous role of Notch1 in breast CSCs expansion. Harrison et al 42 has reported that Notch4 also affects breast CSCs. They performed knockdown of Notch paralog (Notch1 and Notch4) using both ESA þ / CD44 þ /CD24 low and mammosphere prepared from MCF-7 cells, although Notch ICD overexpression was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of primary mammospheres is a reliable in vitro assay to measure stem cell/early progenitor activity and, therefore, to demonstrate the presence of a stem cell population. [50][51][52][53] Because CD44 + CD24 -/ low cells have repeatedly been designated as highly tumorigenic the anti-proliferative activity of trastuzumab against the trastuzumab-refractory JIMT1 cells.…”
Section: Epithelial-to-mesenchymal Transition (Emt) Confers Primary Rmentioning
confidence: 99%
“…Later, numerous studies established that the NOTCH1 signaling pathway plays a role in breast cancer development (22). Recently, many reports have suggested a function of the NOTCH signaling pathway in promoting self-renewal of mammary stem cells and breast cancer stem cells (23)(24)(25)(26). Harrison et al reported that pharmacologic or genetic inhibition of NOTCH reduced stem cell activity in vitro and tumor formation in vivo.…”
Section: Introductionmentioning
confidence: 99%